Usşakilerde Etvar-ı Seb'a - Şengül, Fatma (My University, 2009)
OZET Pir Hasan Hüsâmeddin Uşşaki aydınlatmaya ve öğretilerini yaymaya Uşak şehrinde başlamıştır. Bu sebeple “Uşşaki” olarak bilinir ki, bu “Uşaklı olan kişi” anlamına gelmektedir ve Halvetiyye’den geliştirdiği tarîkata da Halvetiyye-i Uşşakiyye denilmiştir. Uşşaki Tarikatı, nefis mertebesini esas alan tarikatlardan birisidir. Halvetiyye ve Uşşakiyye şeyhleri nefis mertebelerini açıklamak üzere “Etvar-ı Seb’a” adıyla onlarca eser kaleme almışlardır. Bu şeyhlerden birisi de Muhammed Tevfik Uşşaki’dir. Bu tezde onun Etvâr-ı Sûfiyye’sinde nefis mertebeleriyle ilgili ele aldığı konuları ortaya koymaya çalıştık. yye, Halvetiyye, sâlik, nefs, Etvâr-ı Seb’a, seyr u sülûk.

Pir Hasan Hüsâmeddîn Ushshaki started to enlighten and spread his teachings in the city of Ushak. Therefore, he has been known as Ushshaki which means a person who is from Ushak and the path he developed from Khalweti path is called Khalwetiyye-i Ushshakiyye. Ushshaki path is one of the sufi orders which aims the training animal soul. The Khalwetiyye sheikhs and The Ushshakiyye sheikhs have written tens of books named as Atwar-ı Sab’a in order to explain the divine stations of soul. One of the these sheikhs is Muhammed Tevfik Ushshaki. In this thesis we tried to discuss the subject of divine stations as explained in his Atwar-ı Sufiyyah. Key words: Ushshakiyye, Khalwetiyye, seeker (salik), individual soul (nafs), Atwar-ı Sab’a, walking a spritual path to God (sayru suluk)
Keywords: İslam Dini; Tasavvuf